Bunheads - Copeland, Misty (G. P. Putnam's Sons, 2020)
From prima ballerina and New York Times bestselling author Misty Copeland comes the story of a young Misty, who discovers her love of dance through the ballet Coppelia--a story about a toymaker who devises a villainous plan to bring a doll to life. Misty is so captivated by the tale and its heroine, Swanilda, she decides to audition for the role. But she's never danced ballet before; in fact, this is the very first day of her very first dance class! Though Misty is excited, she's also nervous. But as she learns from her fellow bunheads, she makes wonderful friends who encourage her to do her very best. Misty's nerves quickly fall away, and with a little teamwork, the bunheads put on a show to remember. Featuring the stunning artwork of newcomer Setor Fiadzigbey, Bunheads is an inspiring tale for anyone looking for the courage to try something new.